2007
DOI: 10.1016/j.apnum.2006.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Validated solutions of initial value problems for parametric ODEs

Abstract: In initial value problems for ODEs with interval-valued parameters and/or initial values, it is desirable in many applications to be able to determine a validated enclosure of all possible solutions to the ODE system. Much work has been done for the case in which initial values are given by intervals, and there are available software packages that deal with this case. However, less work has been done on the case in which parameters are given by intervals. We describe here a new method for obtaining validated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
195
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 169 publications
(198 citation statements)
references
References 23 publications
1
195
0
1
Order By: Relevance
“…We have demonstrated here the use of a recently developed interval method (Lin and Stadtherr, 2007) for determining mathematically and computationally guaranteed bounds on the population trajectories that are possible for given bounds on the uncertain quantities. Using Monte Carlo analysis, it was also shown that it is possible for these bounds to be quite tight.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have demonstrated here the use of a recently developed interval method (Lin and Stadtherr, 2007) for determining mathematically and computationally guaranteed bounds on the population trajectories that are possible for given bounds on the uncertain quantities. Using Monte Carlo analysis, it was also shown that it is possible for these bounds to be quite tight.…”
Section: Discussionmentioning
confidence: 99%
“…To control the wrapping effect, the state enclosures are propagated using a new type of Taylor model consisting of a polynomial and a parallelepiped (as opposed to an interval) remainder bound. Complete details of the computation of T yj+1 are given by Lin and Stadtherr (2007). An implementation of this approach, called VSPODE (Verifying Solver for Parametric ODEs), has been developed and tested by Lin and Stadtherr (2007), who compared its performance with results obtained using the popular VNODE package (Nedialkov et al, 1999;Nedialkov et al, 2001).…”
Section: Solution Proceduresmentioning
confidence: 99%
See 3 more Smart Citations